2020
DOI: 10.1177/1365480220972873
|View full text |Cite
|
Sign up to set email alerts
|

Organizational building versus teachers’ personal and relational needs for school improvement

Abstract: Organizational building is essential if school leaders are to promote school improvement, but it can be difficult to combine with school leaders’ requirements to satisfy teachers’ personal and relational needs. The the aim of this study is to explore critical aspects when combining organizational building with requirements to satisfy teachers’ personal and relational needs in efforts to strengthen improvement capacity. The paper draws on a 3-year collaborative research project between a research team at a Swed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Future schoolteachers are expected to engage in school development processes by being concerned with overarching topics beyond their own teaching, contributing to school policy making and collaborating with parents and external partners (Liljenberg & Blossing, 2021). These extended requirements correspond to Hoyle (1980) early conception of the 'extended professional'.…”
Section: School Development As Part Of Teachers' Professional Identitymentioning
confidence: 99%
See 1 more Smart Citation
“…Future schoolteachers are expected to engage in school development processes by being concerned with overarching topics beyond their own teaching, contributing to school policy making and collaborating with parents and external partners (Liljenberg & Blossing, 2021). These extended requirements correspond to Hoyle (1980) early conception of the 'extended professional'.…”
Section: School Development As Part Of Teachers' Professional Identitymentioning
confidence: 99%
“…Schools around the world face challenges that require change, improvement and organisational re‐thinking (Liljenberg & Blossing, 2021). Educational policies in Germany have in recent years been targeted at tackling these challenges and improving teacher training in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…Low quality in schools is caused by several factors, including a lack of effective work ethic, quality, quantity, curriculum, and infrastructure provided to support the education process (Figueiró & Raufflet, 2015). Low school quality can also arise due to several problems, including budget problems, lack of facilities, minimal quality, lack of enthusiasm and motivation, below-standard innovation, and a lack of enthusiasm (Liljenberg & Blossing, 2021); (Potterton et al, 2020). Some madrasah teachers do not teach by their educational background or field of knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Drawing his findings from the TALIS instrument, Schleicher (2015) concluded that schools providing their staff with opportunities to participate actively in school decisions and supporting professional development are also more likely to express satisfaction with the terms of their employment contract (cf. Liljenberg & Blossing, 2020).…”
Section: Collaborative Professional Development and Establishing Incl...mentioning
confidence: 99%
“…claimed that teachers need to influence professional knowledge research projects by participating and contributing their experiences to improve teaching or dealing with other problems to address professional needs adequately. Such a process focuses on their personal and relational needs and establishes methods for teachers to communicate their understanding of the curriculum, students' results, and work in teacher groups (Liljenberg & Blossing, 2020).…”
Section: Collaborative Professional Development and Establishing Incl...mentioning
confidence: 99%